2018
DOI: 10.3390/app8101884
|View full text |Cite
|
Sign up to set email alerts
|

Information-Bottleneck Decoding of High-Rate Irregular LDPC Codes for Optical Communication Using Message Alignment

Abstract: In high-throughput applications, low-complexity and low-latency channel decoders are inevitable. Hence, for low-density parity-check (LDPC) codes, message passing decoding has to be implemented with coarse quantization—that is, the exchanged beliefs are quantized with a small number of bits. This can result in a significant performance degradation with respect to decoding with high-precision messages. Recently, so-called information-bottleneck decoders were proposed which leverage a machine learning framework … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…The huge number of lookup tables used in the information bottleneck decoders of [26] can be viewed as a space complexity cost for their computational simplicity. We demonstrate that using the message alignment technique of [7], the required number of tables and, hence, the space complexity of the information, bottleneck SCL decoders can be reduced.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The huge number of lookup tables used in the information bottleneck decoders of [26] can be viewed as a space complexity cost for their computational simplicity. We demonstrate that using the message alignment technique of [7], the required number of tables and, hence, the space complexity of the information, bottleneck SCL decoders can be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that an information bottleneck decoder having a bitwidth as low as 4 bits performs very close to the belief propagation decoder [1]. The idea of information bottleneck decoders was extended to irregular LDPC codes in [7,8]. Design of quantized message passing decoders that utilize information preserving table lookup operations was also addressed in [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, several authors considered a novel approach for decoding of binary LDPC codes [7]- [12]. In these works, a principle was applied which is fundamentally different from state-of-the-art signal processing approaches.…”
Section: Introductionmentioning
confidence: 99%